Modal Analysis of Different Stator Configurations to Mitigate Electromagnetically Excited Audible Noise and Vibrations of Switched Reluctance Motors - Selma Čorović; Rok Benedetič; Damijan Miljavec, (Applied Computational Electromagnetics Society Journal (ACES), 2021)
The primary objective of this paper was to investigate different stator configurations of switched reluctance motors (SRM) in order to mitigate electromagnetically exited audible noise and vibration. We analyzed natural frequencies of different SRM stator configurations by virtue of modal analysis theory. The three-dimensional numerical modeling of SRM stator geometry was performed by using finite element method. Based on the output results, we propose the solutions on how to select an appropriate stator configuration in order to increase its natural frequencies beyond the resonant operational frequency, and thus, to mitigate the resulting audible noise and vibration. The numerical and analytical results are successfully compared to the published data.